Oral Cancer Control in Kerala, India: A Comprehensive Analysis of Policy Documents from 1988 to 2020 - Philip, Phinse M; Kannan, Srinivasan (Asian Pacific Journal of Cancer Care, 2024)
Kerala, India, has been a pioneer in cancer control efforts at the state level. This study conducted a comprehensive review of cancer control policy documents in Kerala from 1988 to 2020 to analyze the structure and function of oral cancer control within the broader cancer control framework. A systematic search of PubMed, government websites, and institutional libraries identified 18 relevant documents. Two cancer-specific policy documents and two health policy documents were included for analysis. The review employed a checklist to evaluate the documents’ content and strategies. The reviewed documents outlined a pragmatic approach to cancer control in a low-resource setting. The concept of the ‘Kerala Cancer Care Grid’ emerged as an innovative strategy to address geographical disparities in access to care. The documents emphasized interdepartmental coordination and partnerships with the private sector and community organizations.